Effects of Human Resource Accounting on Organisational Productivity of Selected Tertitay Institutions in Oyo State - Ige Olubunmi Oladeji; Michael Adeyemi Olayiwola (MultiTech Publisher, 2021)
This study examined the effects of human Resource Accounting on orgnisational productivity of selected tertiary institution in Oyo state. The study focused on staff training, remuneration and development. The population of the study comprised of 74 employees randomly selected from public and private institutions. A structured and validated questionnaire was used for data collection from the respondents. The response rate was 80% of the respondents. Descriptive statistics and correlation were adopted in the analysis of data. The results of regression analysis revealed significant correlation of staff training and development with organisational productivity with p value .000<0.05 level of significant. Similarly, employee remuneration exert a positive significant effect with Organisational productivity with p value .000<.05 level of significant. The findings recommended that management can increase their organisational productivity by investing much in staff training and development and employee remuneration in return will bring a great improvement in organisational productivity of the institutions